Sustainability in project management in the South African context - Chothia, Tasmiyah; Booi, Zanoxolo; Madonsela, Nikiwe (University of Witwatersrand, 2016)
The research study is commissioned to analyse the application of sustainability in project management, with particular reference to the difficulties experienced when applying sustainability into project management that affect the goal of achieving project management and sustainability in South African construction projects. Global warming is considered to be a worldwide concern and the construction industry has been concerning itself with the concept of sustainability in order to minimise their impact on the environment, the resources and their contribution towards global warming. Implementing sustainability into the construction project process assists in reducing these impacts, however there are a range of challenges due to the change from the traditional way of constructing and managing the project. As a result, project managers are faced with difficulties when implementing sustainability into their project management practices which has an impact on their objectives. The study has adopted a mix method research methodology by using both primary and secondary sources in order to achieve its aim and objectives with a limitation to the primary data being information collected only from professional project managers within South Africa. This research uses an inductive approach to collect qualitative data. The study comprised of the collection of data from formulated questions that were in line with the findings of the literature brought to the South African context as well as questions against what the literature was not able to provide for. These questions were presented in the form of an online questionnaire as a survey to a drawn sample of construction project managers registered with the South African Council for Project and Construction Management Professions. The research reports on the data collected from eighty-nine participants with and without sustainable building experience in order to obtain the experienced and the perceived to be experienced challenges. After this process, the data was analyzed through the use of categorization of data and graphs to compare data collected. The findings from this study reveal the significant challenges experienced by project managers when implementing sustainability into their practice. Similarities between what the literature says and what the South African respondents stated were found.
The research study is commissioned to analyze the application of sustainability in project management, with particular reference to the difficulties experienced when applying sustainability into project management that affect the goal of achieving project management and sustainability in South African construction projects.
Keywords: Sustainability in construction industry; Project management--Sustainability